Acupuncture combined with speech rehabilitation training for post-stroke dysarthria: A systematic review and meta-analysis of randomized controlled trials - Qianwen Xie; Xueyin Chen; Jingmin Xiao; Shaonan Liu; Lihong Yang; Jing Chen; Jiaqi Lai; Rui Lan; Yi Chen; Haifang Yang; Xinfeng Guo (Integrative Medicine Research)
Background: The evidence of Acupuncture combined with speech rehabilitation training for post-stroke dysarthria is insufficient and there is no consensus on its efficacy. Methods: We searched seven Chinese and English medicine databases for randomized controlled trials (RCTs) from their inception to November 2019. The primary outcome measure was the clinical response rate, assessed with the Frenchay Dysarthria Assessment (FDA) tool. We assessed risk of bias using the Cochrane risk-of-bias tool. We used GRADE to assess the certainty of evidence (CoE). Results: Thirty studies were included in this systematic review, 23 of which were pooled in meta-analysis. Acupuncture combined with speech rehabilitation training is likely beneficial for was response rate (n = 1685; RR = 1.37; 95% CI [1.29, 1.46], P < 0.01, I2 = 34%; 17 studies, low CoE) compared to speech rehabilitation treatment alone. Conclusion: The combination of acupuncture and speech rehabilitation training may improve total response rate of stroke patients with dysarthria. However, more RCTs with rigorous study design and validated outcome measures are needed to confirm the evidence.